Intranodal Palisaded Myofibroblastoma: A Review of the Literature. (August 2013) - Bhullar, Jasneet Singh; Varshney, Neha; Dubay, Linda
Intranodal palisaded myofibroblastoma is a rare benign primary mesenchymal neoplasm originating from differentiated smooth muscle cells and myofibroblasts. The precise etiology and pathogenesis has not been adequately explained as yet. Very few series and cases have been reported in the literature. Though inguinal region is the commonest site of this rare tumor, but the tumor at other diverse sites have been reported. Because of its rarity, it can be often misdiagnosed and confused with other disorders and more commonly with metastasis. We report an extensive review of literature about intranodal palisaded myofibroblastoma—its characteristics, presentations, features, and management.